ENGAGING WITH MIGRANT LEARNERS AS CO-RESEARCHERS THROUGH PHOTOVOICE: GUIDELINES FOR TRANSFORMING SOCIAL WORK RESEARCH - Mabvira, Agrippa; Pillay, Roshini; Masinga, Poppy (Social Work/Maatskaplike Werk, 2024)
In recent years, photovoice has gained considerable traction as a methodological approach for data collection. This article presents a reflexive account of our utilisation of photovoice for a qualitative doctoral research project that sought to capture the acculturation experiences of 12 immigrant adolescent learners in South Africa. Findings of the study offered rich and thick descriptions of co-researchers’ perspectives on how to foster successful acculturation, which is a testament to how photovoice revolutionises conventional research methodologies. Accordingly, this article argues that by embracing photovoice, social workers can develop more culturally sensitive and effective interventions, rooted in authentic experiences of service users. Therefore, this study aims to educate readers by providing a comprehensive overview of the phases that were undertaken in our photovoice project. In addition, the article, explores the benefits and challenges associated with the application of photovoice, shedding light on the intricacies of participant engagement through visual storytelling and illuminating the ways in which this method can augment research outcomes and amplify the voices of marginalised individuals.